2017
DOI: 10.14740/jem448e
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Resistant Hypertension Among Type 2 Diabetic Patients Attending the National Center for Diabetes, Endocrinology, and Genetics

Abstract: Background: In type 2 diabetic patients, resistant hypertension (RH) is associated with higher cardiovascular diseases (CVDs) and renal diseases; however, a prevalence of RH in the Middle East is unknown. Long duration of uncontrolled blood pressure and diabetes may increase the risk of RH. This study aimed to assess the prevalence of hypertension and RH among adult type 2 diabetic patients, and to determine the relationship between RH and patient demographics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(50 reference statements)
2
2
0
Order By: Relevance
“…An increased body mass index as indicated by overweight and obesity was another important finding which was associated with suboptimal BP control where the prevalence was 56.6% and 63.2%, respectively. This was similar to the findings in Jordan where the prevalence of overweight and obesity was 52.5% and 28.8%, respectively [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An increased body mass index as indicated by overweight and obesity was another important finding which was associated with suboptimal BP control where the prevalence was 56.6% and 63.2%, respectively. This was similar to the findings in Jordan where the prevalence of overweight and obesity was 52.5% and 28.8%, respectively [19].…”
Section: Discussionsupporting
confidence: 91%
“…Uncontrolled blood sugar as shown by HBA1C was 68.2% which can be explained by poor adherence to medication. Elevated cholesterol was found in 50.3%; these findings are almost the same with that of the study done in Jordan (HBA1C (52.5%) and cholesterol (54.9%)) [ 19 ]. Inactivity and consumption of saturated fats in meat and cooking oils are the major factors contributing to dyslipidaemia.…”
Section: Discussionsupporting
confidence: 86%
“…This percentage is remarkably less than our population, in which 43.07% of resistant hypertension patients had IHD. On the other hand, Mohammad A et al reported that 54.6% (77/141) of resistant hypertension patients had IHD [11]. Our data resource could explain our results since most data were from a cardiac center.…”
Section: Discussionmentioning
confidence: 48%
“…Our study's prevalence of resistant hypertension in patients with T2DM was consistent with other studies. Solini A et al reported a prevalence of 17% in Italy [10], and Mohammad A et al reported a prevalence of 16% in Jordan [11]. These articles reported a significant association between resistant hypertension and T2DM.…”
Section: Discussionmentioning
confidence: 99%